Cutaneous Nocardiosis Simulating Cutaneous Lymphatic Sporotrichosis - Pedro Secchin; Beatriz Moritz Trope; Larissa Araujo Fernandes; Glória Barreiros; Marcia Ramos- (Karger Publishers, 2017)
Sporotrichosis is the subcutaneous mycosis caused by several species of the Sporothrix genus. With worldwide occurrence, the State of Rio de Janeiro is presently undergoing a zoonotic sporotrichosis epidemic. The form of lymphocutaneous nocardiosis is rare, being caused especially by Nocardia brasiliensis. It appears as a nodular or ulcerated lesion, with multiple painful erythematous nodules or satellite pustules distributed along the lymphatic tract, similar to the lymphocutaneous variant of sporotrichosis. We present a 61-year-old man who, after an insect bite in the left leg, developed an ulcerated lesion associated with ascending lymphangitis, nonresponsive to previous antibiotic therapies. The patient was admitted for investigation, based on the main diagnostic hypothesis of lymphatic cutaneous sporotrichosis entailed by the highly suggestive morphology, associated with the epidemiologic information that he is a resident of the city of Rio de Janeiro. While culture results were being awaited, the patient was medicated with sulfamethoxazole-trimethoprim to cover CA-MRSA and evolved with total healing of the lesions. After hospital discharge, using an ulcer fragment, an Actinomyces sp. was cultivated and N. brasiliensis was identified by molecular biology. The objective of this report is to demonstrate a case of lymphocutaneous nocardiosis caused by N. brasiliensis after a probable insect bite. Despite the patient being a resident of the State of Rio de Janeiro (endemic region for sporotrichosis), it is highlighted that it is necessary to be aware of the differential diagnoses of an ulcerated lesion with lymphangitis, favoring an early diagnosis and appropriate treatment of the illness.